Ali Aksara Teks Manuskrib Salinan Tarjuman Al Mustafid Dalam Makna Surah Al Fatihah - Sinaga, Sania Arisa; Hidayat, Muhammad; Manurung, Ade Irma; Harahap, Rida Wahyuni; Br Sembiring, Fitri Handayani; Damanik, Nia Syahfitri (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
Tarjuman Tafsir al-Mustafid is one of the Quran interpretations written in Arab Jawi (an old Malay-style writing) which is considered as the earliest and the most complete Quran interpretation in Indonesia. This interpretation was written by Sheikh Abdur Rauf al-Singkili, during the reign of Queen Safiyatuddin. There are two views about the writing source of this interpretation, first as the translation of a Baidhawi interpretation and second as the translation of Jalalain and Al-Khazin books. The method applied in the writing of this interpretation can be analyzed from its interpretation and meaning. In term of its interpretation, this book used tahlili (analysis) as it explains the verses in sequence and their content from various aspects, while in term of its meaning it used ijmali (global) as its explanation is in accordance with the meaning of the verses it describes. Keywords: Ali Aksara, Tarjuman Al-Mufasid